Pemahaman Terperinci Mengenai Berbagai Model Kurikulum di Dunia Pendidikan Sesuai Perkembangan Zaman - SITI AULIA FEBRIANTI (PT. Syaelindra Karya Nusantara, 2024)
Curriculum In the world of education is the main foundation that forms the foundation of education. There are various curriculum models that are pillars in forming the teaching and learning process. A good curriculum is one that suits students’ needs, is dynamic, can change with the development of the times, science and technology, culture, value systems, and is in accordance with the needs of society. This article aims to understand in depth the various curriculum models, present an in-depth understanding of each approach, and analyze their relevance in the current educational context. Through a comprehensive understanding, this article will explore the essence of curricula that influence education globally.